1997
DOI: 10.1038/bjc.1997.582
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of surgery and adjuvant chemotherapy for primary gastric lymphoma stage II

Abstract: Summary The standard management of primary gastric lymphoma (PGL) (stage 11) has not been established despite the use of various treatment modalities. The present prospective trial of combined surgery and chemotherapy for the treatment of PGL (stage 11) included 25 consecutive patients treated between July 1978 and December 1993. Twenty-one patients were treated with total gastrectomy and four with partial gastrectomy; this was followed by post-operative chemotherapy with m-VEPA (vincristine, cyclophosphamide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Takenaka et al showed that the best treatment for the non-perforated stage I and II gastric malignant lymphoma is a gastrectomy combined with chemotherapy. 3 The frequency of complications such as bleeding or a perforation in unresected tumors with gastrointestinal malignant lymphoma has been reported to be between 12% and 20%, 2,11 and the rate of perforation of the gastric malignant lymphoma was 0%-5%. 1,2,9 Since this complication often occurs after chemotherapy, the prognosis of patients with a perforation is poor.…”
Section: Discussionmentioning
confidence: 98%
“…Takenaka et al showed that the best treatment for the non-perforated stage I and II gastric malignant lymphoma is a gastrectomy combined with chemotherapy. 3 The frequency of complications such as bleeding or a perforation in unresected tumors with gastrointestinal malignant lymphoma has been reported to be between 12% and 20%, 2,11 and the rate of perforation of the gastric malignant lymphoma was 0%-5%. 1,2,9 Since this complication often occurs after chemotherapy, the prognosis of patients with a perforation is poor.…”
Section: Discussionmentioning
confidence: 98%
“…The principal reason for this is a low radical resection rate: 20% in stage II 1E and 0% in stage IVE, and of course the fact that no formal adjuvant therapy regimen has been used in these patients. This figure necessitates more intense attention in the future and surgical management must be followed by a planned adjuvant therapy that may produce complete remission and long-term disease-free survival in patients with stage II disease [18] or even in patients with relapse [19].…”
Section: Discussionmentioning
confidence: 99%
“…Patients whose disease was clinical stage I E and is pathologic stage II should receive postresection chemotherapy to enhance long-term freedom from recurrence. Some series report a 90% to 100% freedom from recurrence rate and a 70% to 90% long-term survival rate with this combination approach [18,19]. Gastric perforation or uncontrolled hemorrhage at presentation is an indication for surgery.…”
Section: Therapy For H Pylori Infectionmentioning
confidence: 97%
“…Results vary from a success rate less than 50% to a long-term disease-free survival rate of 70% [16•,17]. Chemotherapy adds to the long-term recurrence-free survival rate in patients treated initially with primary surgery whose pathologic disease stage is II or higher [3,18,19]. Standard regimen The most common regimen used to treat large-cell lymphoma is known by the acronym CHOP and consists of intravenous cyclophosphamide, 750 mg/m2, on day 1; intravenous doxorubicin, 50 mg/m2, on day 1; intravenous vincristine, 1.4 mg/m2, on day 1 (maximum dose, 2 mg); and oral prednisone, 100 mg daily on days 1 through 5.…”
Section: Chemotherapymentioning
confidence: 99%